Konsep Perancangan Dalam Meningkatkan Kualitas Lingkungan Fisik Kawasan Perdagangan dan Jasa Jalan Jenderal Sudirman Kota Salatiga - Nurgianto, Nurgianto (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Jalan Jenderal Sudirman area in Salatiga has a strong character and a strategic function as a developing commercial area. With the presence of modern markets and star hotels besides having traditional market, this area is now a contender in the regional market. However, the increase of activity intensity which is taking place has not been accompanied by improvement of the environmental carrying capacity, resulting in deteriorating public infrastructures, traffic problem and cluttered informal activities, potentially leading to the degradation of the physical environment. These problems may accumulate and lowers the city’s competitiveness, therefore this study tries to formulate a concept of urban design through qualitative descriptive design to revive the environmental quality of Jalan Jenderal Sudirman area in Salatiga. The concept is established based on good urban design criteria employing SWOT analysis to accommodate the potential strengths, weaknesses, threats and opportunities in the study area. The analysis suggested an applicable design concept for Jalan Jenderal Sudirman which includes the following components: provision of refined infrastructures, better management of the informal sector, along with traffic management.